Syringocystadenoma Papilliferum and Basal Cell Carcinoma Arising in Nevus Sebaceous - Jiang J; Chen Y; He Q; Yang J; Zhang Z; Yang H; Zhang H; Yang C (Dove Medical Press, 2022)
Jingjing Jiang *, Yujuan Chen *, Qi He, Jiao Yang, Zhengzhong Zhang, Hao Yang, Huan Zhang, Chuan Yang Department of Dermatology, Affiliated Hospital of North Sichuan Medical College, Nanchong, People's Republic of China*These authors contributed equally to this workCorrespondence: Zhengzhong Zhang, Department of Dermatology, Affiliated Hospital of North Sichuan Medical College, No. 1 Maoyuan South Road, Shunqing District, Nanchong City, Sichuan Province, 637000, People's Republic of China, Tel +8618080339898, Email laowaiaeo@163.comAbstract: Nevus sebaceous (NS) is a benign congenital hamartoma with the potential to develop into a secondary benign or malignant skin tumors. Two or more skin tumors rarely arise simultaneously from a single NS lesion. Herein, we report a case of syringocystadenoma papilliferum and basal cell carcinoma arising in an NS, based on dermoscopic, reflectance confocal microscopic, and histopathological findings.Keywords: nevus sebaceous, syringocystadenoma papilliferum, basal cell carcinoma, dermoscopy, reflectance confocal microscopy